Caribbean Economic Overview 2002 : Macroeconomic Volatility, Household Vulnerability, and Institutional and Policy Responses - Caribbean Group for Cooperation in Economic Development (World Bank, Washington, DC, 2013)
This report uses an analytical framework that take into account the effect of natural disasters as well as country size in measuring the serious implications macroeconomic or aggregate volatility (marked period-to-period variations in measures of macroeconomic performance, such as GDP growth) has for individuals and households in Caribbean countries. The report is organized as follows: Chapter 1 reviews the recent economic and social development of the Caribbean. Chapter 2 begins by characterizing volatility of aggregate income and consumption growth and by employing regression analysis to assess the relative importance of the different factors that would be expected to determine macroeconomic volatility in the Caribbean. The chapter also examines factors that might be expected to influence the extent to which macroeconomic volatility is absorbed or amplified-that is, the extent of financial market development, the behavior of remittances, and the size and volatility of external capital flows. Chapter 3 addresses the broad question of how macroeconomic volatility in the Caribbean affects households and their income and consumption,; and how households respond to shocks and how such effects differ by socioeconomic status. Chapter 4 reviews the extent to which countries and households in the Caribbean region use market insurance, self-insurance, self-protection, or other outside protection mechanisms to deal with aggregate shocks. It points to policy areas for further attention